Strategi Kepala Sekolah Dalam Meningkatkan Efikasi Diri Guru MTs TMI Putri Al-Amien Prenduan - Sitti Manalurrahmah; Muru'atul 'Afifah (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2024)
This study aims to analyze the principal's strategies in enhancing teachers' self-efficacy and their impact on professionalism and institutional development. Using a qualitative approach with a case study method at MTs TMI for Female Al-Amien Prenduan, data were collected through observation, interviews, and documentation. The findings reveal that the principal implemented strategies such as mentoring, training, motivation, role modeling, a reward and punishment system, and regular evaluations. These strategies effectively increased teachers' confidence, encouraged instructional innovation, and strengthened the institution’s reputation and overall quality